Nurses' experiences during the COVID-19 pandemic in Iran: a qualitative study - Vahid Zamanzadeh; Leila Valizadeh; Mohammad Khajehgoodari; Farzaneh Bagheriyeh (BMC, 2021)
Abstract Background Nurses are at the forefront of patient care during infectious disease pandemics and they play a key role in treating and preventing the upward trend of the disease. Hence, it is crucial to consider their experiences in designing action plans to combat coronavirus disease 2019 (COVID-19). Since there is not enough data in this regard, the current study aimed to investigate the nurses' experiences in caring for patients with COVID-19 in Iran. Methods In this descriptive qualitative study, a total of 20 nurses were selected by purposive sampling. Semi-structured interviews were conducted and analyzed using qualitative content analysis to collect data. Results Data analysis revealed four main themes, including 'duality in the form of care,' 'confusion and ambiguity in care planning', 'workload', and 'social isolation in spite of positive image.' Conclusion Our findings indicated that the nurses experienced a range of paradoxes during the COVID-19 pandemic; these paradoxes included distraction from providing care due to focus on marginal factors in spite of empathy and cooperation in nurses, the presence of volunteer support staff despite the lack of equipment, lack of scientific information and the unreliability of online information, overload in the hospital due to insufficient facilities and equipment, and the physical avoidance of people in the community in spite of social support for nurses in the media. The results of this study can lead to a clear understanding for managers and healthcare policymakers in the country and aid them in taking optimal measures to support nurses and improve the quality of nursing care against COVID-19.